Vaginal fertility-sparing surgery and laparoscopic sentinel lymph node detection in early cervical cancer. Retrospective study with 15 years of follow-up. (August 2020) - Gil-Ibañez, B.; Glickman, A.; Del Pino, M.; Boada, D.; Fuste, P.; Diaz-Feijoo, B.; Pahisa, J.; Torne, A.
Abstract: Objective: The aim of this study was to evaluate the oncological outcomes of vaginal fertility-sparing surgery plus laparoscopic sentinel lymph node biopsy in patients with early cervical cancer over a 15-years period. Patients and methods: From March 2005 to April 2018, 38 patients diagnosed with early stage cervical cancer underwent vaginal fertility-sparing surgery at the Hospital Clínic, Barcelona, Spain. Patients with FIGO stage IA1 with lymphovascular space invasion and stage IA2 underwent simple trachelectomy and patients with stage IB1 underwent radical vaginal trachelectomy. All cases underwent laparoscopic sentinel lymph node biopsy. In the first 19 cases, laparoscopic bilateral pelvic lymphadenectomy was completed immediately after sentinel lymph node biopsy. Clinical and oncological follow-up data were collected. Results: The median age at diagnosis was 33.5 years (range 22–44). Simple trachelectomy was performed in seven cases (18.4%) and vaginal radical trachelectomy in 31 (81.6%). Nineteen patients were exclusively treated with laparoscopic sentinel lymph node biopsy and 19 with sentinel lymph node biopsy plus laparoscopic bilateral pelvic lymphadenectomy. There were no significant differences between the two lymph node assessment groups regarding histology and tumour size. The median follow-up was 73 months (range 1–160 months). There were 4 recurrences (3 patients with IB1 and 1 with IA2). Two occurred in the sentinel lymph node biopsy group and 2 in the sentinel lymph node biopsy plus laparoscopic bilateral pelvic lymphadenectomy group. All the recurrences were diagnosed in patients with adenocarcinoma and in 3 patients without lymphovascular space invasion. Conclusion: Vaginal fertility-sparing surgery combined with laparoscopic sentinel lymph node biopsy seems to be a safe oncological procedure in selected patients with early stage cervical cancer. Further studies are needed to clarify the role of sentinel lymph node biopsy in fertility- sparing surgery in cervical cancer. Adenocarcinoma histology seems to be an important risk factor for recurrence.